2022
DOI: 10.3847/2041-8213/ac6670
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of ATLAS17jrp as an Optical-, X-Ray-, and Infrared-bright Tidal Disruption Event in a Star-forming Galaxy

Abstract: We hereby report the discovery of ATLAS17jrp as an extraordinary tidal disruption event (TDE) in the star-forming galaxy SDSS J162034.99+240726.5 in our recent sample of mid-infrared outbursts in nearby galaxies. Its optical/UV light curves rise to a peak luminosity of ∼1.06 × 1044 erg s−1 in about a month and then decay as t −5/3 with a roughly constant temperature around 19,000 K, and the optical spectra show a blue continuum and very broad Balmer lines with FWHM ∼ 15,000 km s−1, which grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 53 publications
(87 reference statements)
4
21
2
Order By: Relevance
“…The results of the spectral analysis are reported in Table 5 and are shown if Figure 7. These results are all consistent with the X-ray analysis already presented in the recent discovery paper of AT 2017gge (Wang et al 2022). Additionally, in order to investigate the origin of the delayed X-ray flare as produced by a newly formed accretion disk, we have modelled the data with the TBABS*ZASHIFT*DISKBB model (right panel of Figure 7, red solid line).…”
Section: The X-ray Spectral Analysissupporting
confidence: 87%
See 4 more Smart Citations
“…The results of the spectral analysis are reported in Table 5 and are shown if Figure 7. These results are all consistent with the X-ray analysis already presented in the recent discovery paper of AT 2017gge (Wang et al 2022). Additionally, in order to investigate the origin of the delayed X-ray flare as produced by a newly formed accretion disk, we have modelled the data with the TBABS*ZASHIFT*DISKBB model (right panel of Figure 7, red solid line).…”
Section: The X-ray Spectral Analysissupporting
confidence: 87%
“…The detected X-ray emission has a transient nature, with only upper limits (grey triangles in the Figure ) for the first 170 days from the discovery of AT 2017gge and showing the peak around 200 days. Furthermore, no X-rays have been detected in the recent XRT observations taken at ∼1684 days (see Wang et al 2022). Such a delayed X-ray brightening with respect to the optical/UV peak has already been observed in some TDEs, specifically, ASASSN-14li (Pasham et al 2017;Gezari et al 2017), ASASSN-15oi (Holoien et al 2018), AT 2019azh (Liu et al 2022) and OGLE16aaa (Kajava et al 2020;Shu et al 2020), which have shown ∼30 days, 1 year, 200 and 140 days of delay in the X-ray emission, respectively.…”
Section: The X-ray Light-curvementioning
confidence: 86%
See 3 more Smart Citations